Carbon doped GaN layers grown by Pseudo‐Halide Vapour Phase Epitaxy. Issue 8 (27th April 2017) - Siche, Dietmar; Zwierz, Radoslaw; Kachel, Krzysztof; Jankowski, Nadja; Nenstiel, Christian; Callsen, Gordon; Bickermann, Matthias; Hoffmann, Axel
Abstract : Highly carbon doped GaN layers were grown by a modified Halide Vapour Phase Epitaxy, using HCN as Ga and C precursor. Oxygen and silicon background level was increased, especially at V‐pits, resulting in high n‐type conductivity. SIMS, PL and μRaman measurements revealed this behaviour. Homogeneous dopant incorporation was hindered, as long as V‐pit formation cannot be prevented by a much higher effort in substrate preparation, to decrease stresses and to improve coalescence. Abstract : Pseudo‐Halide Vapour Phase Epitaxy (PHVPE) was utilized to grow thick carbon doped GaN layers to study their suitability as semi‐insulating (SI) substrates. With in‐situ waste gas analysis by FTIR spectroscopy, the carbon doping from the HCN precursor gas was indirectly controlled in a wide range up to 5 × 10 19 cm –3 . The grown layers were characterized by Scanning Electron Microscopy (SEM), Secondary Ion Mass Spectroscopy (SIMS), Photoluminescence (PL), Micro‐Raman‐Spectroscopy, Hall effect measurement, and High Resolution X‐Ray Diffractometry (HRXRD). Similar to the impurity incorporation (O, Si, Mg and Zn), carbon distribution proved to be inhomogeneous, due to its increased incorporation on facets of so‐called V‐pits.